Academic Stress Among Male and Female Students After the Covid-19 Pandemic - Ifdil, Ifdil; Lela, Lela; Syahputra, Yuda; Fitria, Linda; Zola, Nilma; Pratiwi Fadli, Rima; Barseli, Mufadhal; Eka Putri, Yola; Amalianita, Berru (COUNS-EDU: The International Journal of Counseling and Education, 2022)
This study aims to describe the condition of students' academic stress and examine differences in academic stress in male and female students after the Covid-19 pandemic. This research is a comparative research obtained through random sampling. The sample of this study was 118 students consisting of several high schools in Padang City. Data was collected with an academic stress scale with 57 items. The analysis technique uses the item response theory (IRT) approach with the Rasch Model analysis. This study examines descriptive and differences with Welch with the help of WINSTEPS Version 4.7.0. The results show that there is a significant difference between male and female academic stress. Other findings found that women's academic stress tended to be higher than that of men, and what was interesting from this data was that there was a woman who was at the highest logit or an outlier, meaning that this woman needed to be given intervention to reduce her stress by providing individual counseling services. Based on the results of this study it is hoped that school counselors will focus more on women for academic stress prevention programs.